Oncogene mutations in non-small cell lung cancer patients in Iran: a study of their association with programmed death ligand-1 expression - Zahra Abrehdari-Tafreshi; Majid Pirestani; Zahra Mosaferi; Nasser Rakhshani; Ehsan Arefian (The Egyptian Journal of Bronchology)
Abstract Background Lung cancer is a globally pervasive and deadly disease, claiming more than 1 million lives annually. Therefore, the identification of mutations in crucial cancer-related genes is paramount for guiding optimal chemotherapy strategies. The distribution of EGFR, KRAS, ALK, and ROS1 mutations varies across diverse ethnic populations. Nonetheless, there is limited data available on the prevalence of these mutations and their correlation with PD-L1 expression among Iranian lung cancer patients. Aim This study involved an analysis of EGFR, KRAS, ALK, and ROS1 gene mutations in lung cancer patients, followed by an assessment of the correlation between PD-L1 expression and clinicopathological variables. Methods Mutational profiling was conducted by examining EGFR (exons 18–21) and KRAS (exon 2) through pyrosequencing. Detection of ALK and ROS1 rearrangements, alongside PD-L1 expression, was carried out using immunohistochemistry techniques. Results EGFR mutations were identified in 23.4% of cases, exhibiting a notably higher occurrence in females (p = 0.001). KRAS mutations were present in 7.1% of cases, with no significant association found between KRAS mutations and sex (p = 0.229). ALK rearrangements were found in 4.9% of cases, while ROS1 rearrangements were present in 0.6% of patients. The overall prevalence of PD-L1 protein expression was 36.85%. Notably, PD-L1 expression was detected in 24.8% of cases with EGFR mutations, 20% of cases with KRAS mutations, 64.7% of cases with ALK rearrangements, and in 100% of cases with ROS1 rearrangements. Conclusion Although no correlation was found between PD-L1 expression and EGFR, KRAS mutations, and ROS1 rearrangements, a noteworthy association was identified between ALK rearrangements and elevated PD-L1 expression.